Determination of risks and solutions in sewage works - Bulut, Selda (Nova Science Publishers, Inc., 2023)
In today's world, the rapid pace of globalization and industrialization has often brought serious environmental and water challenges. With the shortage of clean drinking water, the quality of life of people has decreased and the level of welfare has decreased. However, the uncontrolled population growth revealed the importance of water and sewerage works for reasons such as migration. Sewage systems are systems that enable the collection of waste and rainwater consisting of canals and connected pipes with modern techniques and conveying them to wastewater treatment plants. The main purpose here is to collect the system, which distributes drinking and potable water to the subscribers after using it, with modern techniques and to make it harmless, especially to the environment. While all these processes are taking place, the risks arising from dangers such as physical, chemical, biological and psychosocial hazards that employees are exposed to in these workplaces, hazards arising from working in closed areas, hazards arising from working with construction equipment, ergonomics, excavation works, and contact with wastewater will be investigated. These risks play an important role in the emergence of health problems and occupational accidents in sewerage works. © 2023 Nova Science Publishers, Inc. All rights reserved.
Keywords: Occupational health and safety; Risks and solution; Sewage works